A stolen childhood A dark past, a terrible secret, a girl without a future - Watson, Casey (London: Harper Element, 2015)
Bestselling author and teacher Casey Watson shares the horrifying true story of Kiera Bentley, a 12-year-old girl with a deeply shocking secret she$1 (Bs too young to even understand. When Casey first meets Kiera, a small slight girl who$1 (Bs just lashed out at a fellow pupil in assembly, she immediately senses something$1 (Bs wrong. Something in Kiera$1 (Bs eyes alerts Casey that this is an (3z(Bold head on young shoulders(3y(B, and with Kiera$1 (Bs constant tiredness and self-soothing habit of pulling her hair out, she follows her instinct and takes Kiera under her wing. At first the answer seems simple enough; Kiera$1 (Bs parents aren$1 (Bt together and they don$1 (Bt get on, which makes life hard for Kiera as she$1 (Bs so close to her dad. But as the weeks roll on, Casey begins to understand that there$1 (Bs something much darker going on behind closed doors. And when she finally learns the truth, she$1 (Bs terrified she won$1 (Bt be able to save Kiera from it. s
Vendor supplied metadata.
Keywords: books